The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1080/03655230701600053
|View full text |Cite
|
Sign up to set email alerts
|

Treatment results for 84 patients with base of tongue cancer

Abstract: The main treatment options were radiotherapy for primary lesions < or = T2 and surgery for primary lesions > or = T3. Overall disease-specific 5-year cumulative survival rate was 59.8%, but there was no significant difference in survival rate at each stage between the two treatments. Among patients who died of the primary disease, the area that was most difficult to control was the superior margin of the lateral wall of the oropharynx (n=7). The incidence of contralateral or retropharyngeal lymph node metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…A limited number of prior studies have reported RPLN involvement in oropharyngeal carcinoma, with a variable incidence (Table 4) [12][13][14][20][21][22][23]34]. In our series of 402 patients, the rate of radiological RPLN involvement was 10%.…”
Section: Discussionmentioning
confidence: 55%
“…A limited number of prior studies have reported RPLN involvement in oropharyngeal carcinoma, with a variable incidence (Table 4) [12][13][14][20][21][22][23]34]. In our series of 402 patients, the rate of radiological RPLN involvement was 10%.…”
Section: Discussionmentioning
confidence: 55%
“…They found that the risk was higher for patients with posterior and lateral pharyngeal wall cancers (29% for lateral and posterior wall vs 0% for others sites). In 2007, Yoshimoto et al34 reported their series of 84 patients with base of tongue cancer. In this series, 2 patients had RPLN metastases at the time of diagnosis and 2 more developed recurrent cancer in the RPLN.…”
Section: Anatomymentioning
confidence: 99%
“…Data regarding the incidence of retropharyngeal lymph node (RP LN) metastases in oropharyngeal cancer are limited due to the difficulty of surgical access [1] with pathological data based upon small series [2,3]. Imaging studies report a variable incidence (2-21%) of RP LN metastases [4][5][6][7][8][9][10][11]. MRI is superior to CT for the detection of RP LNs [1,12,13].…”
mentioning
confidence: 99%